The Development of Flipped Learning Model Based on MyBrilian to Support Planned Online Learning - M. J. Dewiyani Sunarto (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
The Covid 19 pandemic period has changed the learning system, including the presence of online learning. Literature reviews from various sources state that the Flipped Learning model is an alternative model for planned online learning. Even so, the Flipped Learning model cannot be implemented directly, but it must be adapted to the conditions where students learn. The development of the Flipped Learning model in this study is supported by a Moodle-based e-learning campus, which is called MyBrilian, through the following syntax: (1) Introduction, (2) Exploration, (3) Study, (4) Exposure, and (5) Assessment. This study involved 66 students of Information System study program of Universitas Dinamika who took Basic Mathematics courses. The instrument used is the Lesson Plans, Student Learning Materials and Test Instruments. Data analysis through statistical descriptive and qualitative descriptive techniques. Based on the data analysis, it can be concluded that the learning is classified into increased knowledge on a high scale, namely N-Gain of 0.7, and based on student response questionnaire, it shows satisfactory results in each syntax. The conclusion is that the flipped learning model can be adopted as an implementation of planned online learning, by adjusting to local learning conditions and with the support of technology.